If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 81 = 6n + 42 + 7n Reorder the terms: 81 = 42 + 6n + 7n Combine like terms: 6n + 7n = 13n 81 = 42 + 13n Solving 81 = 42 + 13n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-13n' to each side of the equation. 81 + -13n = 42 + 13n + -13n Combine like terms: 13n + -13n = 0 81 + -13n = 42 + 0 81 + -13n = 42 Add '-81' to each side of the equation. 81 + -81 + -13n = 42 + -81 Combine like terms: 81 + -81 = 0 0 + -13n = 42 + -81 -13n = 42 + -81 Combine like terms: 42 + -81 = -39 -13n = -39 Divide each side by '-13'. n = 3 Simplifying n = 3
| 5w=w-64 | | 14-3*g=32 | | 2y-5=(-2y)+7 | | 1(2-7)=3(1-x) | | 0.16-0.02(x+1)=-0.04(1-x) | | (3s+t)(t-s)= | | 1+12k+6=31 | | .8n=.10n | | 26=4x | | 6(y+3)=6y+4 | | 1(y-1)=1(1-8) | | 25+7p=3(3p+3) | | -2z-6=-8 | | (3s-t)(t-5)= | | 0.5k-(k+0.5)=0.75(K+2) | | 5-3(-1+6)=9-1+8*-1 | | 5z+3=-7 | | 5-3(-1+6)=9-1+8*1 | | 5(3-4)=1(x-1) | | r+3+2r=21 | | 2x+7=3y+9 | | 9t-8-2(t+3)=-21 | | 4(-6x-12)=192 | | 3x^2=-13x-12 | | 2x-29=x+57 | | 1(-9-3)=1(-2-y) | | 9XS=9 | | 5(x-3)+8=43 | | -(x+4)+7x=0 | | 9x^2-3ax+1=0 | | 4x-8=2x+5 | | x^2-3ax+1=0 |